2014
DOI: 10.1088/0268-1242/29/8/082001
|View full text |Cite
|
Sign up to set email alerts
|

Reversible UV induced metal–semiconductor transition in In2O3thin films prepared by autowave oxidation

Abstract: We have prepared thin indium oxide films by the autowave oxidation reaction. Measurements of temperature dependence of resistivity, Hall carrier concentration and Hall mobility have been conducted in the temperature range 5-272 K. Before ultraviolet (UV) irradiation, the indium oxide film had a semiconductor-like temperature dependence of resistivity ρ and the ratio of ρ (5 K)/ρ(272 K) was very limited (∼1.2). It was found that after UV irradiation of the In 2 O 3 film, the metal-semiconductor transition (MST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
1
8
0
2
Order By: Relevance
“…The band gap of the indium oxide films, depending on the method of preparation, can vary from 3.5 eV (355 nm) to 4 eV (310 nm) [5], which is consistent with our measurements [45].…”
Section: Resultssupporting
confidence: 91%
“…The band gap of the indium oxide films, depending on the method of preparation, can vary from 3.5 eV (355 nm) to 4 eV (310 nm) [5], which is consistent with our measurements [45].…”
Section: Resultssupporting
confidence: 91%
“…In addition, the indium oxide film had a limited ratio of resistances measured at 5 K and 272 K (~1.2). Furthermore, it has been shown that ultraviolet irradiation can induce MST in the indium oxide film [36]. Thus, we expect that the weak localization effect and the related negative magnetoresistance can be observed in thin In 2 O 3 films prepared by autowave oxidation.…”
Section: Introductionmentioning
confidence: 91%
“…As known, the foundation of this type of device is TCO (Transparent Conducting Oxide). Up to now, lots of n-type TCO have been reported 6,7 , Such as ZnO, In 2 O 3 , but the lack of p-type TCO restricted the development of the transparent photoelectric device. Although GaN etc.…”
mentioning
confidence: 99%